Why should they care? The role of institutional investors in the market for corporate global responsibility - Clark, G; Hebb, T (Pion Ltd., 2005)
Institutional investors, primarily pension funds, drive global financial markets. The result is investors vulnerable to the risks companies face in global consumer and capital markets. Though some market risks are inevitable, others, such as reputation risk, can be mitigated through increased corporate social and environmental standards and the increased transparency that such higher standards demand. The transparency necessitated by reputation management has a dual role in monitoring corporate behaviour and providing all stakeholders (internal and external) with the information to evaluate corporate behaviour. Driving this process is the belief that higher standards of corporate responsibility pay off for investors over the long term both through potential equity premia and through risk reduction. This paper presents a model for understanding how and why institutional investors may encourage firms to adopt higher standards. To illustrate our argument, we refer to the experience of the UK Universities Superannuation Scheme (USS) strategy of corporate engagement and the attempts of the USS to encourage firms to raise their environmental standards by focusing on the climate change impacts of pension-fund investments. Investor engagement in corporate responsibility offers an insight into the role of investors in global-standard setting and global citizenship.